Governance Quality and Innovation Capability: Insights from Indonesia - Irsan Hardi; M. Shabri Abd. Majid; Talbani Farlian; M. Saleh; Andri Suriansyah; Cut Syazalisma; Naftaly Mose (Grimsa Journal of Business and Economics Studies, 2026)
Innovation is a key driver of national competitiveness, and its advancement increasingly relies on the strength of governance quality. However, empirical evidence linking governance performance to national innovation outcomes in the Indonesian literature remains limited. This study addresses this gap by assessing how the Worldwide Governance Indicators (WGI), used as a proxy for governance quality, affect Indonesia’s innovation capability as measured by the Global Innovation Index (GII). The analysis also incorporates additional factors that commonly influence innovation capabilities, including economic growth, foreign direct investment, and the labor force. By adopting a decomposition model to evaluate the individual contributions of each WGI dimension, and employing Gaussian Identity-link GLMs and robust least squares methods, the results show that governance quality overall has a positive and significant effect on Indonesia’s GII. When each component of the WGI is assessed individually, most dimensions display positive effects, with voice and accountability, political stability, and rule of law showing notably significant impacts. These findings imply that strengthening governance structures, particularly in transparency, stability, and legal certainty, is essential for advancing Indonesia’s innovation capability.